Bioinformatics : Design and Implementation - White, Alexis (United States : Murphy & Moore Publishing, 2022)
Bioinformatics is an interdisciplinary field that focuses on developing methods and software tools for understanding large and complex biological data. It consolidates the disciplines such as biology, computer science, information engineering, mathematics, and statistics to analyze and interpret biological data. Some of the subfields of bioinformatics are computational biology, genetics, genomics, proteomics, transcriptomics, phylogenetics, metabolomics, systems biology, structural analysis, molecular modeling and pathway analysis. Bioinformatics is applied in various sectors such as molecular medicine, personalized medicine, preventative medicine, gene therapy, drug development, waste cleanup, etc. This book is a compilation of chapters that discuss the most vital concepts and emerging trends in bioinformatics. It elucidates new techniques and their applications in a multidisciplinary manner. For all readers who are interested in this field, the case studies included in this book will serve as an excellent guide to develop a comprehensive understanding.
Includes index.
Includes bibliographical references.
Keywords: Bioinformatics; Molecular biolog